Anopheles (Nyssorhynchus) striatus, a new species of the Strodei Subgroup (Diptera, Culicidae) - Sant'Ana,Denise Cristina (2017)
ABSTRACT A new species of the genus Anopheles Meigen (Diptera: Culicidae), Anopheles (Nyssorhynchus) striatus n. sp., preliminary designated as Anopheles CP Form, from Brazil, is here validated and described using morphological characteristics of the egg, fourth-instar larva, pupa, female and male genitalia. The species is morphologically more similar to species of the Strodei Subgroup of Anopheles (Nyssorhynchus) than to any other species of the subgenus Nyssorhynchus Blanchard. However, adult female that can be misidentified with Anopheles (Nyssorhynchus) galvaoi Causey, Deane & Deane if the identification is mainly based on the ratio of dark and white scales of the hindtarsomere 2. In addition, the characterization of the new species includes aspects of its bionomics, and geographical distribution. The new species is known from Espírito Santo, Minas Gerais and Paraná states, in Brazil. Diagnostic characters for the identification of the species are provided.